White Women in the 1960s Freedom Movement, From Memory to History: The writing of “Shiloh Witness,” a chapter in Deep in Our Hearts (2000) - Joan Browning (Transatlantica)
In this article, Joan C. Browning, a white female veteran of the 1960s Civil Rights Movement, reflects on the writing of an autobiographical chapter she wrote for a collective book published in 2000 (Deep in Our Hearts: Nine White Women in the Freedom Movement). Focusing on the dialectical tension between memory and history, she discusses several questions ranging from the genesis of the book project to her regrets at censoring herself in anticipation of criticisms. The essay sheds new light on her personal experience of the Southern Civil Rights Movement—especially her participation in the Albany Freedom Ride in 1961, the role of religion in her commitment to the Movement, and her feelings about the movement’s evolution after 1964. The author describes the profound impact of the Movement on her life and her identity as a white, Southern woman. In addition to this personal account, she probes into the scientific issues of writing the history of the Civil Rights Movement, i.e. the place of women in historiography, the relationship between historians and their living subjects, the question of privacy, the tension between objectivity and subjectivity, and the difficult negotiation between history and activism in the self-writing process.